Hybrid layer difference between sixth and seventh generation bonding agent - Grace Syavira Suryabrata (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
Since etching is completed at the same stage as priming and bonding, when applying the sixth and seventh generation bonding, the exposed smear layers are constantly surrounded by primer and bonding and cannot collapse. The smear layer and the depth of penetration of resin bonding in dentinal tubules are completely integrated into hybrid layer. The purpose of this laboratory research was to study the penetration depth of two self etching adhesive. Fourteen samples of human extracted teeth were divided into two groups. Each groups consisted of seven samples, each of them was treated with sixth generation bonding agent and the other was treated with seventh generation bonding agent. The results disclosed that the penetration into dentinal tubules of seventh generation bonding agent was deeper than sixth generation bonding agent. Conclusion: bond strength will improve due to the increasing of penetration depth of resin bonding in dentinal tubules.